The influence of the combined impairments and apical mesh surgery on the biomechanical behavior of the pelvic floor system - Xue, Xianglu; Zheng, Qiuyu; Gao, Zhenhua; Shen, Jihong; Yao, Tingqiang (Frontiers in Bioengineering and Biotechnology, 2024)
The prolapse mechanism of multifactorial impairment of the female pelvic floor system and the mechanics of the pelvic floor after apical suspension surgery are not yet understood, so we developed biomechanical models of the pelvic floor for normal physiological state (0°) and 90° pathological state. Methods Under different types and levels of the impairments, and uterosacral suspensions, the possible changes in the morphometric characteristics and the mechanical characteristics of suspension and support functions were simulated based on the biomechanical models of the pelvic floor. Results After the combined impairments, the descending displacement of pelvic floor cervix, and the stress and displacement of perineal body reached maximum. After the surgical mesh implantation, the stresses of normal pelvic floor were concentrated on the uterine fundus, the cervix, and the top of the bladder, and the stresses of 90° pathological state pelvic floor were concentrated on the uterine fundus, the uterine body, the cervix, the middle of the posterior vaginal wall and the bottom of the perineal body. Conclusions After the combined impairments, the biomechanical support of the bladder and sacrococcyx in the anterior (0°) and 90° pathological state pelvic floor system is diminished, the anterior vaginal wall dislodges from the external vaginal opening, and the posterior vaginal wall forms "kneeling" profiles. The pelvic floor system may evolve with a tendency toward the cervical prolapse with anterior and posterior vaginal wall prolapse and eventually prolapse. After the surgical mesh implantation, the cervical position can be better restored, but the load of combined impairment of the pelvic floor is mainly borne by the surgical mesh suspension, the biomechanical support function of pelvic floor organs and sacrococcyx was not repaired by the physiological structure and the results of uterosacral suspension alone may be poor.